Employee engagement among Gen Y engineers in Malaysian Engineers Consultants Service (ECS) firms - Mansor, Zuraina; Loke, Yen Theng (RMP Publications, 2018)
This study provided additional understanding between the areas of work life and employee engagement specifically among Gen Y engineers who are working with Malaysia Engineers Consultant Service (ECS) Firms. According to the board of engineers, there was about 58,994 Graduate Engineers who are currently working in this knowledge-intensive nature and relatively high labor costs area. The job satisfaction and engagement were important issues for them. The study aimed to examine the relationship between subscales of areas of work life (workload, control, rewards, community, fairness and value-fit) and elements of employee engagement (Vigor, Dedication and Absorption) among the engineering consultant. The findings suggested that the best predictor for employee engagement is Value-fit. The study also proposed that leader or manager should prevent mismatches between the organization’s values and the values of its employee. In other words, organization must make sure there is shared value between employer and employees.